2021
DOI: 10.1177/2325967121994550
|View full text |Cite
|
Sign up to set email alerts
|

Failed Surgery for Patellar Tendinopathy in Athletes: Midterm Results of Further Surgical Management

Abstract: Background: Tendon injuries are commonly seen in sports medicine practice. Many elite players involved in high-impact activities develop patellar tendinopathy (PT) symptoms. Of them, a small percentage will develop refractory PT and need to undergo surgery. In some of these patients, surgery does not resolve these symptoms. Purpose: To report the clinical results in a cohort of athletes who underwent further surgery after failure of primary surgery for PT. Study Design: Case series; Level of evidence, 4. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…In cases where conservative measures and primary surgery have failed, revision surgery remains an option. Maffulli et al reported a 68.2% success rate in returning to competition in less than 1 year, with an 18% complication rate, based on a recent publication involving 22 athletes who underwent revision surgery after a failed previous intervention 70 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where conservative measures and primary surgery have failed, revision surgery remains an option. Maffulli et al reported a 68.2% success rate in returning to competition in less than 1 year, with an 18% complication rate, based on a recent publication involving 22 athletes who underwent revision surgery after a failed previous intervention 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that most patients with PT can be effectively managed nonoperatively, there is limited literature available on surgical options after a failed prior surgery. Surgical failure, as defined by Maffuli et al, is characterized by persistent pain and inability to RTS after at least 1 year postsurgery 70 .…”
Section: Revision Proceduresmentioning
confidence: 99%
“…Surgical exploration is difficult for patients to accept due to high cost, large investment and large trauma. [7][8]…”
Section: Discussion Tendon Injury and General Examinationmentioning
confidence: 99%
“…In addition, failure after surgery means that this option can bring about a poor prognosis. 3,16 Regenerative medicine with autologous expanded bone marrow-derived mesenchymal stem cell (BM-MSC) therapy has recently been introduced in the management of tendon pathology. 6 In 2021, we published the 6-month follow-up results of a prospective, double-blind, randomized, 2-arm, parallel, active-controlled, phase 1/2, singlecenter clinical study investigating the effects of ultrasound-guided intratendinous and peritendinous injections of BM-MSCs or leukocyte-poor PRP (Lp-PRP) on clinical outcomes in younger patients (age, 18-48 years) with patellar tendinopathy.…”
mentioning
confidence: 99%
“…In patellar tendinopathy, elite and nonelite running and jumping athletes 9 , 14 experience anterior knee pain and reduced function, often for prolonged periods. 16 Although modification of training and implementation of load management programs may be effective, 5 it is still unclear what the optimal strategies are. 17 In addition, the results of nonoperative management are unpredictable, and returning to sport is not certain despite rigorous adherence to rehabilitation programs.…”
mentioning
confidence: 99%